2020
DOI: 10.1021/acschemneuro.0c00242
|View full text |Cite
|
Sign up to set email alerts
|

Solid Lipid Nanoparticles Enhanced the Neuroprotective Role of Curcumin against Epilepsy through Activation of Bcl-2 Family and P38 MAPK Pathways

Abstract: Oxidative stress of neurons caused by a series of complex neuropathological processes will induce certain neurodegenerative disorders including epilepsy. Curcumin (Cur) is an effective natural antioxidant compound; however, the poor bioavailability obstructs its neural protective applications. In this study, Cur is encapsulated in solid lipid nanoparticles (SLNs) for better neuroprotective efficacy. In vitro study certified that Cur-SLNs functioned obviously better against neuronal apoptosis than Cur, by signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…In a kainic acid rat model, curcumin prevented activation of astrocytes and neuronal death, and a recent study showed a mechanism involving the Bcl2 family and P38 MAPK pathways (323). The anti-epileptic effects were probably associated, according to the authors, to lower IL10RB, CXCL17 and nicastrin levels.…”
Section: Epilepsymentioning
confidence: 91%
“…In a kainic acid rat model, curcumin prevented activation of astrocytes and neuronal death, and a recent study showed a mechanism involving the Bcl2 family and P38 MAPK pathways (323). The anti-epileptic effects were probably associated, according to the authors, to lower IL10RB, CXCL17 and nicastrin levels.…”
Section: Epilepsymentioning
confidence: 91%
“…In a mouse model of chronic epilepsy, the incorporation of curcumin with CS-alginate STPP NPs significantly increases its corresponding effects on cell death, cognitive defects, and glial activation, consistently with the solubility of the compound (Hashemian et al, 2017). Curcumin-loaded SL NPs induce neuroprotective effect by reducing apoptosis via upregulation of erythropoietin and klotho, reduction of tumor necrosis factor-α (TNF-α), and the subsequent activation of P38 MAPK pathways (Mansoor et al, 2018;Huang et al, 2020). It has also been shown that treatment with piperine-loaded CS-STPP NPs strongly inhibits the progression of epileptic symptoms by suppressing cell death and astrocyte stimulation compared to non-loaded piperine-treated mice (Anissian et al, 2018).…”
Section: Epilepsymentioning
confidence: 93%
“…The results of this study showed that this nanoliposome considerably enhanced the latency to the onset and reduced the duration of seizures in animal models of epilepsy and epileptic seizures. In another in vivo study, Huang, Lin, Chen, Chang, and Lin (2020) and Huang et al (2020) have reported antiepileptogenic effects of solid lipid nanocarriers containing Cur through reducing neuronal apoptosis, activation mechanisms of Bcl‐2 family, and P38 MAPK. These results indicated that this nanoformulation might be considered a promising therapeutic approach for the treatment of epilepsy.…”
Section: Cur Nanoformulations As Promising Strategies For the Treatme...mentioning
confidence: 99%